Tinjauan Hukum Terhadap Fenomena Kawin Kontrak : Perspektif Hukum Islam dan Hukum Positif Indonesia - Wardhani, Sartika Dwi Kusuma; Ambarsari, Ririen Indria Dian; Bidasari, Anindya; Suciati; Fahmi, Tishlahatul Ulya Muflihal (WARKAT, 2025)
Marriage is a sacred and everlasting agreement. The phenomenon of contract marriage raises issues regarding the legal regulations that bind it. Contract marriage is a marriage based on an agreement to live together for a certain period of time and compensation to certain parties. The desire to fulfill biological needs is one of the objectives of implementing contract marriage. This study uses a normative legal method which is the main reference for the regulations in force in Indonesia. The results of the study explain that contract marriage has no legal force. The legal consequences that arise are that a wife cannot obtain the general rights of a legal wife, and children born from contract marriage do not have a civil relationship with their father.